Republic of Korea : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that the Republic of Korea is enjoying its longest uninterrupted period of economic expansion since the Asian crisis. Growth reached 5 percent in 2006, buoyed by strong exports, and is only expected to slow marginally to 4 3/4 percent this year. The current account is expected to remain broadly in balance. The impact of the ongoing global financial turbulence has so far been manageable but downside risks to the outlook have increased, with the nascent consumption recovery vulnerable to a downturn in asset markets.